HUBUNGAN EXPLOSIVE POWER OTOT LENGAN BAHU DENGAN KEMAMPUAN SHOOTING UNDER RING PADA TIM BOLABASKET PUTRA SMAN 6 PEKNBARU - Ibrahim '; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACK : This Researchis a correlation study. This research was conducted at the SMAN 6 Pekanbaru men basketball team. Data were obtained and collected by the independent variable tests (explosive power arm shoulder muscles) and test the dependent variable (shooting under ring capability). The data obtained were analyzed using product moment correlation analysis.Explosive relationship Sleeve Shoulder Muscle Power Shooting Capability under Ring with the SMAN 6 Men's Basketball Team Pekanbaru. Problem identification results showed that men's basketball player SMAN 6 Pekanbaru yet under the ring shooting ability not Maximum. It initials due to the lack of the factors associated with the development of these techniques. By therefore then with lifted Research carried problem "Does the Relations explosive power arm shoulder muscles with shooting capability under the ring at SMAN 6 men's basketball team Pekanbaru?" The proposed research hypotheses on Research husband is "There are Relationship explosive power arm shoulder muscles with shooting capabilities under men's rings on basketball team SMAN 6 Pekanbaru." This study aims to determine the relationship label explosive power arm shoulder muscles with shooting capability under the ring on men's basketball team SMAN 6 Pekanbaru.Results of the analysis showed that there is a relationship explosive power arm shoulder muscles with shooting under ring capabilities at the SMAN 6 Pekanbaru men basketball team. Based on product moment correlation analysis produced a correlation coefficient (r) of 0.5686, which means there is a correlation between the independent variable and dependent variables and the t test result of tcount 2.4883 and ttable 1,771. Means tcount > ttable so it can be concluded that H0 is rejected and Ha is accepted and shows that a significant relationship between the two variables.Keywords: Explosive power arm shoulder muscles, Shooting under ring capability